2014
DOI: 10.1080/10410236.2014.924045
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence Memorable Message Narratives: A New Exploratory Research Study Into Young Adult Sexual Narratives

Abstract: Abstinence for most adolescent-aged college students relates to several factors, including strong religious beliefs, an aversion to taking risks, high career expectations, or limited attractiveness. Young adults receive hundreds of messages from various sources; therefore, understanding their memorable sexual messages is essential. This exploratory research uses an interpretive method to unravel the memorable sexual narratives of 65 virgin respondents. Findings yield two primary themes: involuntary abstinence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Couture-Carron, & Maticka-Tyndale, 2016). For others, abstinence could result from a lack of desire, a prioritization of other interests or ambitions, or situational factors, such as not having a partner at all (Cooke-Jackson, Orbe, Johnson, & Kauffman, 2015;Sprecher & Treger, 2015). Still, for others, sexual abstinence can be a combination of these different factors.…”
Section: Discussionmentioning
confidence: 99%
“…Couture-Carron, & Maticka-Tyndale, 2016). For others, abstinence could result from a lack of desire, a prioritization of other interests or ambitions, or situational factors, such as not having a partner at all (Cooke-Jackson, Orbe, Johnson, & Kauffman, 2015;Sprecher & Treger, 2015). Still, for others, sexual abstinence can be a combination of these different factors.…”
Section: Discussionmentioning
confidence: 99%
“…Forced/Involuntary Abstinence (Involuntary celibacy): Persistent or recurrent abstinence from all sexual contacts cause significant interpersonal problems and marked distress. It differs from conscious abstinence when observed for internal attitudes and belief system of the person [38][39][40]. Participation in pornography: Participation in sexual activity involving video recording of self [41].…”
Section: Deviant Sexual Behavior (Dsb) and Substance Abuse (Sa)mentioning
confidence: 99%
“…Several pro-social messaging campaigns have found that narratives offer a particularly effective way to communicate with adolescents about health topics (Cooke-Jackson et al, 2015; Gilliam et al, 2016; Willis et al, 2018). Quinn et al (2007), for example, found in preparation for a media campaign to reduce violence among middle-school students that teens desire spokespersons who can share firsthand stories about violence and its consequences: “It should be someone that has gone through it” (p. 363).…”
Section: Introductionmentioning
confidence: 99%